Architectural regeneration - Orbasli, Aylin, 1968-; Vellinga, Marcel (Wiley Blackwell, 2020)
"The book will address the different perspectives, scales and tools of architectural regeneration by means of detailed overviews of the current state of thinking and practice, with case studies from around the world used as examples to support the theoretical arguments. The chapters will focus on different scales and types of regeneration (urban, rural, suburban, temporary); discuss the economic, planning, policy and social contexts of regeneration processes; and investigate the role of the design process and the architect in them. Addresses the different perspectives, scales and tools of architectural regeneration by means of detailed overviews of the current state of thinking and practice Provides a thorough overview and discussion of architectural regeneration, in practice and theory Builds a theoretical framework under which the practice of architectural regeneration can be understood Includes extensive case studies from around the world as examples to support theoretical arguments"--